2000
DOI: 10.1557/proc-625-123
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Dye Distribution With Ink-Jet Dye Doping of Polymer Organic Light Emitting Diodes

Abstract: In this work we investigate the lateral dye distribution resulting from the dye doping of a thin polymer film by ink-jet printing (IJP) for the integration of color organic light emitting diodes (OLED's). The dye is found to segregate into distinct outer rings following rapid droplet evaporation, while slower evaporation rates are found to significantly reduce (or eliminate) this effect. The dye segregation phenomena are found to depend critically on the mechanisms of droplet evaporation. Good dye uniformity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…As mentioned in the introduction, ring formation can be reduced by using a low vapor pressure solvent. 18 However, Fig. 2b shows that in case of ethyl acetate, which has, according to Table 1, the highest vapor pressure of all solvents used, ring formation was not more pronounced than with any of the other solvents used.…”
Section: Single Solventsmentioning
confidence: 81%
See 1 more Smart Citation
“…As mentioned in the introduction, ring formation can be reduced by using a low vapor pressure solvent. 18 However, Fig. 2b shows that in case of ethyl acetate, which has, according to Table 1, the highest vapor pressure of all solvents used, ring formation was not more pronounced than with any of the other solvents used.…”
Section: Single Solventsmentioning
confidence: 81%
“…16,17 Similar studies on the lateral dye distribution in ink-jet printed organic polymer light-emitting diodes suggested that a lower rate of evaporation eliminates the deposition of dye into distinct outer rings. 18 In another application, the polymer was dissolved in a mixture of two solvents, the first solvent having a high boiling point and a low solubility for the polymer, and the second solvent having a low boiling point and a high solubility for the polymer. The dissolving potential of the solvent gradually decreases during evaporation and the polymer precipitates before a ring is formed.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Uniform deposits were obtained by using a very low vapor pressure solvent, e.g., dimethylsulfoxide (DMSO). [36] Another display-related field where inkjet technology is used, is the fabrication of color filters for liquid-crystal displays (LCDs). Here, every pixel is imprinted with inks containing differently colored dyes or pigments to create a multicolor display.…”
Section: Manufacturing Of Pled Displays and Liquid-crystal Display Comentioning
confidence: 99%
“…So far, investigations concerned with minimizing and eliminating this problem for different kinds of polymers have mainly focused on optimizing the evaporation rate and solvent system. [23,24,[27][28][29] However, the interaction between the solvent and the polymer has received less attention, even though it contributes to the resulting thin film topography, in particular for conjugated polymers.…”
mentioning
confidence: 99%